Children Exposure assessment to patulin through the intake of apple based products - Pereira, C. (2014)
Nowadays, food safety is of major concern since more chemicals are present in our environment. Food is an important route of exposure to contaminants as mycotoxins. Patulin (PAT) is a mycotoxin present mainly in apple based products which are widely consumed by children. Children are a vulnerable part of the population due to, in part, their physiology, a fairly restricted diet and a higher intake relative to their body weight. Within the safety evaluation procedure of any chemical substance, one crucial step is the dietary exposure assessment. Exposure assessment combines data on concentrations of a chemical substance present in food with the quantity of those foods consumed. Online software to access consumption data are a very useful tool for exposure assessment. The Open Platform for Clinical Nutrition (OPEN) is a Web-based application that provides clinical dietitians and the general population with an online dietary assessment and diet planning tool. It can be used with any food composition dataset that complies with the EuroFIR standards for data harmonisation. In Portugal no data are available on children consumption and data on mycotoxins occurrence in baby foods are scarce. The main objectives of this study were to: i) determine the contents of patulin in apple based foods intended for children, ii) develop tools and procedures for the collection of individual food consumption data for children, iii) test the above mentioned tools and procedures within a pilot dietary survey and iv) analyse the collected data and evaluate the tools and procedures used. For these purposes, 15 samples of apple based foods (juices and purees) analysed for patulin contents (μg/kg) by an accreditated high-performance liquid chromatography and ultraviolet detection method. The children food consumption survey was undertaken using a food diary through the OPEN applied to 20 children aged between 0 to 36 months. Parents were asked to record detailed information about all food and beverages consumed during 3 days. In order to evaluate the exposure, a daily intake will be expressed as μg PAT / kg of body weight / day. For this aim, data on the patulin content will be added to the Portuguese food composition database and applied by the OPEN. We will also consider a provisional tolerable weekly intake (PTWI) of 0.43 μg PAT /kg of body weight / day as a referential value for patulin. Preliminary results of this study shows that apple based products presented patulin contents are all below the legislated limit for patulin (<10 μg/kg). Consumption and exposure assessment results will be discussed. This study reported, for the first time, the use of an online platform for children exposure assessment to patulin through the intake of apple based products in Portugal.